Answer:
[tex]\frac{12}{\sqrt{10} +\sqrt{7} +\sqrt{3} }=\frac{6\sqrt{147} +6\sqrt{63}-6\sqrt{210} }{21 }[/tex]
Step-by-step explanation:
[tex]\frac{12}{\sqrt{10} +\sqrt{7} +\sqrt{3} }[/tex]
[tex]=\frac{12\left( \sqrt{10} -\left( \sqrt{7} +\sqrt{3} \right) \right) }{(\sqrt{10}+(\sqrt{7} +\sqrt{3 } ))( \sqrt{10} -( \sqrt{7} +\sqrt{3}))}[/tex]
[tex]=\frac{12\left( \sqrt{10} -\sqrt{7} -\sqrt{3} \right) }{\sqrt{10^2} -(\sqrt{7} +\sqrt{3})^2}[/tex]
[tex]\frac{12\left( \sqrt{10} -\sqrt{7} -\sqrt{3} \right) }{10-(10+2\sqrt{21} )} }[/tex]
[tex]=\frac{12\left( \sqrt{10} -\sqrt{7} -\sqrt{3} \right) }{-2\sqrt{21} }[/tex]
[tex]=\frac{-6\left( \sqrt{10} -\sqrt{7} -\sqrt{3} \right) }{\sqrt{21} }[/tex]
[tex]=\frac{-6\left( \sqrt{10} -\sqrt{7} -\sqrt{3} \right) }{\sqrt{21} } \times\frac{\sqrt{21} }{\sqrt{21} }[/tex]
[tex]=\frac{-6\sqrt{21} \left( \sqrt{10} -\sqrt{7} -\sqrt{3} \right) }{21 }[/tex]
[tex]=\frac{-6\sqrt{210} +6\sqrt{147} +6\sqrt{63} }{21 }[/tex]
[tex]=\frac{6\sqrt{147} +6\sqrt{63}-6\sqrt{210} }{21 }[/tex]
Remark:
You can simplify moreover if you want to.